Fluoroethylamine Engineering for Effective Passivation to Attain 23.4% Efficiency Perovskite Solar Cells with Superior Stability. Issue 30 (23rd June 2021) - Su, Hang; Zhang, Jing; Hu, Yingjie; Du, Xinyi; Yang, Ying; You, Jiaxue; Gao, Lili; (Frank) Liu, Shengzhong
Abstract: Defects in perovskite layers usually cause nonradiative recombination, impairing device performance and stability. Here, fluoroethylamine (FC2 H4 NH3, FEA) is integrated into the perovskite film to passivate defects. By engineering of different amounts of fluorine in the molecule, it is found that when 2‐fluoroethylamine (1FEA), in which one F bonds to the first carbon atom at the end of the molecule's structure, is used, the F atoms appear to be distributed throughout the bulk to the very surface. When 2, 2‐difluoroethylamine (2FEA) and 2, 2, 2‐trifluoroethylamine (3FEA) are used, F is prone to distribution in the bulk of the perovskite film, while there appears to be no detectable F content on the surface. With the FEA passivation, the nonradiative recombination is suppressed, the carrier‐lifetime is improved to 840.01 ns, and the film‐air interface offers greater hydrophobicity, especially in the case of 1FEA, where because it is distributed throughout the film thickness, it passivates more defects and delivers the highest efficiency, as much as 23.40%. The device with 3FEA shows the best environmental stability; specifically, the bare cell without any encapsulation maintains 87% of its initial efficiency after exposure to the ambient environment for 1200 h. Abstract : Fluoroethylamine passivates defects in perovskite films as a result of F distribution throughout the bulk and even at the surface. The nonradiative recombination in perovskite films using derivatives of this compound is suppressed, the carrier‐lifetime is prolonged, and the film–air interface offers greater hydrophobicity. The corresponding solar cells deliver high efficiency of up to 23.40%. The unencapsulated device shows good environmental stability, maintaining 87% of its initial efficiency after exposure to the ambient environment for 1200 h.